RETRACTED: Technology of stabilizing parameters of twocolor light-emitting diodes - Kuldashov Obbozjon; Ismoilov Ma’murjon; Komilov Abdullajon; Ergashev Shokhboz; Maxmudov Isroiljon; Tadjibayev Ilxomjon; Madaminov Muhriddin (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001